Neoplasias endócrinas múltiplas - Guimarães, J (2010)
The knowledge of genetics has increased in recent years and has led to important changes in management of hereditary diseases. Multiple endocrine neoplasia is characterized by the occurrence of benign or malign tumours involving two or more endocrine glands and two major forms are recognized: MEN1 and MEN2. All these forms of MEN are inherited as autosomal dominant syndromes. In this article we briefly review the clinic, diagnosis and treatment for the MEN1 and MEN2 and the indications for genetic testing.